Determination of Phenolic Acids in Sugarcane Vinasse by HPLC with Pulse Amperometry - P. V. Freitas; D. R. da Silva; M. A. Beluomini; J. L. da Silva; N. R. Stradiotto (Journal of Analytical Methods in Chemistry)
A reversed-phase liquid chromatographic separation with pulsed amperometric detection of phenolic acids at a glassy carbon electrode is described. Chromatographic separation was carried out in isocratic conditions using 0.20 mol·L−1 acetic acid (pH 5.0)/water (80 : 20, v/v) as mobile phase under constant working potential mode of 0.80 V. Chromatographic peaks presented high resolution and separation. Calibration curves exhibited excellent correlation coefficients, above 0.995. Linear ranges of the analytes, in mg L−1, were of 0.018–18 (gallic acid), 0.146–19 (vanillic acid), 0.13–17 (caffeic acid), 0.016–16 (ferulic acid), and 0.008–17 (p-coumaric acid), respectively. Limits of detection ranged from 1.6 to 97 μg·L−1 and precision varied in 1.73–3.78% interval. Concentrations of 19 ± 0.51 mg·L−1 and 7.8 ± 2.5 mg·L−1 were found for vanillic and caffeic acids, respectively, in a sugarcane vinasse sample. Gallic, ferulic, and p-coumaric acids were not detected. Recovery results demonstrated that the proposed method is accurate, and it can be used to detect and quantify phenolic acids in sugarcane vinasse without any influence of interferents.